Structural and functional study on cysteine 495, coordinating ligand to T1Cu site in multicopper oxidase CopA. (October 2021) - Tang, Wenwei; Liu, Haoxiang; Zeng, Xinping
Abstract: Excessive intake of manganese seriously affects human health. Manganese oxidizing bacteria can efficiently remove manganese, among which manganese oxidase plays a decisive role. Multicopper oxidase, one of the manganese oxidases, has 4 copper binding sites, among them, T1Cu coordinates with two histidine, one cysteine and one axial residue, mainly transferring electrons from the substrate to T2Cu and T3Cu. Here, we conducted site-directed mutagenesis on T1Cu coordinating 495 amino acid site from cysteine to aspartic acid, histidine and methionine in multicopper oxidase CopA from Brevibacillus panacihumi MK-8, through the enzyme kinetics and structure models, finding that the enzyme catalytic efficiency ( k cat / K m ) of the mutated C495H with Mn 2+ and ABTS reached 9.03 min −1 mM −1 and 8863 s −1 mM −1, 1.47 times and 1.67 times that of CopA. And it was found strain Rosetta-pET- copA C495H could remove 91.67% manganese after 7-day culture, which was 11.65% higher than the original strain. To sum up, these results provide a vision for the future application of protein engineering in biological manganese removal. Highlights: Research highlights: T1Cu coordinating Cys495 was mutated to Asp, His and Met in multicopper oxidase CopA. Structure and function of proteins were analyzed by enzyme kinetics and Discovery Studio. The mutant strain Rosetta-pET- copA C495H could remove 91.67% of manganese after 7-day culture.